2020
DOI: 10.3390/agronomy10040520
|View full text |Cite
|
Sign up to set email alerts
|

Do Soil Warming and Changes in Precipitation Patterns Affect Seed Yield and Seed Quality of Field-Grown Winter Oilseed Rape?

Abstract: Increasing air and soil temperatures and changes in precipitation patterns as consequences of climate change will affect crop production in agricultural ecosystems. The combined effects of soil warming and altered precipitation on the productivity and product quality of oil crops are not yet well studied. Winter oilseed rape (OSR) (Brassica napus L., cv. Mercedes) was field-grown under elevated soil temperature (+2.5 °C), reduced precipitation amount (−25%), reduced precipitation frequency (−50%) both separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The adaptation of agriculture to the changing climate conditions and adoption of (innovative) sustainable practices will be necessary to reduce the negative consequences, such as reduced yields and crop failure. In this context, Drebenstedt et al [18] assessed changes in soil temperature and precipitation patterns on crop production in agricultural systems in Germany. Their results showed that oilseed rape performed well under moderate changes in soil temperature and rainfall regimes; hence, stable seed yields were observed, with no negative impact on seed nutrient quality.…”
Section: Effect Of Climate Change and Agricultural Practicesmentioning
confidence: 99%
“…The adaptation of agriculture to the changing climate conditions and adoption of (innovative) sustainable practices will be necessary to reduce the negative consequences, such as reduced yields and crop failure. In this context, Drebenstedt et al [18] assessed changes in soil temperature and precipitation patterns on crop production in agricultural systems in Germany. Their results showed that oilseed rape performed well under moderate changes in soil temperature and rainfall regimes; hence, stable seed yields were observed, with no negative impact on seed nutrient quality.…”
Section: Effect Of Climate Change and Agricultural Practicesmentioning
confidence: 99%
“…37 Therefore, the climate suitability of crops and their changing trend in the context of climate change is receiving increasing attention, as rising air temperatures and variability in rainfall patterns affect agricultural ecosystems. 38,39 The livelihood of millions of people is expected to be impacted by changing weather conditions, 40 and banana serves as a daily staple. 41 The extent to which agricultural systems will be affected by climatic conditions differs between crops, regions, and management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the climate suitability of crops and their changing trend in the context of climate change is receiving increasing attention, as rising air temperatures and variability in rainfall patterns affect agricultural ecosystems 38,39 …”
Section: Introductionmentioning
confidence: 99%
“…However, information on its agronomic traits, ability to withstand various stresses, and critical nutrient requirements are scarce. Such a lack of knowledge especially occurs for crops in Mediterranean areas, where stresses including drought were shown to reduce grain, oil yields, and quality to a variable extent [8,[12][13][14][15][16][17], where the effect on oil content was similarly shown to be negligible in other species [18]. Most later reports have shown that a plant density higher than 100 plant m −2 for Evening Primrose is a prerequisite to achieving high yields when the water supply is adequate, but little information is available for water-limited conditions.…”
Section: Introductionmentioning
confidence: 99%